The Effectiveness of Community Engagement Program Towards Urban Poor Community Development: A Study Of MSU MyNeighbours Program - Shufri Johari; Zakmalisa Erna Md Zaki; Noraihan Mohamad; Ain’Shamimi Arifin (ConCEPt - Conference on Community Engagement Project, 2024)
MyNeighbours initiative has gained significance in recent years, collaborating with Management and Science University (MSU) to support the urban poor. HeARTS, aiming to realize Sustainable Development Goal (SDG) 11: Sustainable Cities and Communities, employs its community project, MyNeighbours, to promote community and collaboration. MyNeighbours, themed "Nurturing Generation, Building Society," aims to enhance the economic capabilities of the urban poor through knowledge and skills. The program offers free courses such as basic business design, basic sewing, make up, a food costing guide, cooking and baking workshop, establishing a knowledge transfer bridge between the university and the community. This research aims to assess the effectiveness of the MyNeighbours program on the perceptions of 40 urban poor regarding their standards of living, entrepreneurship, skills and knowledge. By exploring these factors, the study aims to provide insights into the significance of the MyNeighbours program for the urban poor. To gather the data, the researchers employed structured interviews, utilizing the qualitative descriptive method implemented through questionnaires, which are essentially interviews. The data collection involved face-to-face interviews, drawing upon previously collected data in the form of videos and voice notes. Most of the interviewees expressed that the MyNeighbours program played a crucial role in enhancing their standard of living, enabling them to sustain themselves. A significant number of respondents who participated in the program provided positive feedback, stating that it contributed to their improvement and proficiency in managing their businesses. The program exhibited a favorable impact on individuals' skills, knowledge, and the development of a supportive community. The research successfully achieved its objective, as it established a positive correlation between the effectiveness of the MyNeighbours program and the respondents' standard of living, entrepreneurship, skills, and knowledge.